Legal Analysis of Protection in Mass Employment Termination Due to Company Bankruptcy (Case Study of PT Sritex) - Emmanuela Komala Sari (Media Hukum Indonesia (MHI), 2026)
The bankruptcy of large companies in Indonesia gives rise to legal and social issues, particularly concerning mass layoffs and the protection of workers’ rights. This condition becomes increasingly critical in labor-intensive industries with a large workforce, as seen in the case of PT Sritex. This study aims to analyze legal protection for workers and examine the synchronization between the Bankruptcy Law and the Job Creation Law. The method used is normative juridical research with statutory and case approaches, supported by qualitative analysis of secondary data. The results indicate a lack of regulatory synchronization, leading to uncertainty in layoff procedures, as well as suboptimal fulfillment of workers’ rights due to the dominance of secured creditors and the limited assets of the bankruptcy estate. Therefore, regulatory harmonization and the strengthening of the roles of the government and curators are necessary to ensure more equitable legal protection for workers.